Terminal Films. - Christiansen, Steen (Journal of the Fantastic in the Arts, 2014)
This paper analyzes two films, The Ring and Pulse, as examples of "terminal films"--a recent development in the science fiction / horror hybrid genre. I suggest that these terminal films articulate an anxiety of the precarious ontological status of the human in a posthuman world. Employing the concepts of affect and contagion, the films are shown to question and blur the boundaries between biology and technology. In this way, these two films participate in a larger cultural shift away from a conception of human being as a fixed, stable entity into an understanding of the human as part of a larger assemblage.